Native American spirituality : a critical reader - Irwin, Lee, 1944- (University of Nebraska Press, 2000)
Presents a collection of fourteen essays by both Native and non-Native scholars that address Native American spirituality in the twenty-first century, and discusses both traditional religion and Native Christianity, pedagogical practices, and more.